2014
DOI: 10.2337/db13-1015
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29 Fine-tunes the Expression of Key FOXA2-Activated Lipid Metabolism Genes and Is Dysregulated in Animal Models of Insulin Resistance and Diabetes

Abstract: MicroRNAs (miRNAs) have emerged as biomarkers of metabolic status, etiological factors in complex disease, and promising drug targets. Recent reports suggest that miRNAs are critical regulators of pathways underlying the pathophysiology of type 2 diabetes. In this study, we demonstrate by deep sequencing and real-time quantitative PCR that hepatic levels of Foxa2 mRNA and miR-29 are elevated in a mouse model of diet-induced insulin resistance. We also show that Foxa2 and miR-29 are significantly upregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 47 publications
4
97
0
1
Order By: Relevance
“…Increasing evidence has suggested that miRNAs play key roles in insulin resistance and are widely involved in the progression of type 2 diabetes [14,15]. In the present study, we found that miR-499-5p was reduced in the livers of db/db mice and HFD-fed mice and was accompanied by impaired insulin signaling and glycogen synthesis.…”
Section: Discussionsupporting
confidence: 61%
“…Increasing evidence has suggested that miRNAs play key roles in insulin resistance and are widely involved in the progression of type 2 diabetes [14,15]. In the present study, we found that miR-499-5p was reduced in the livers of db/db mice and HFD-fed mice and was accompanied by impaired insulin signaling and glycogen synthesis.…”
Section: Discussionsupporting
confidence: 61%
“…miR-29 signaling reportedly targets adipocyte marker LPL expression in liver lipogenesis and lipogenic gene expression in high fat diet-mediated diabetic mice [17,35]. In this study, declined expression of PPARγ2, LPL and adipokine leptin explained the phenomenon that miR-29a transgenic mice had low adipogenic activities in bone tissue.…”
Section: Accepted Manuscriptmentioning
confidence: 43%
“…For example, expression of miR-29a/b/c was elevated in muscle, fat, and/or liver of diabetic rats [86], fa/fa rats, and high-fat diet-fed mice [87]. Overexpression of miR-29a/b/c in 3T3-L1 adipocytes decreased insulin-stimulated glucose uptake by inhibiting p85alpha and AKT activation [86,88], and led to insulin resistance through mechanisms not involving AKT as the direct target of the miRNA [86].…”
Section: Mirna Dysregulation In Insulin-sensitive Peripheral Tissuesmentioning
confidence: 99%